CLAMP in context a critical study of the manga and anime - Cavallaro, Dani (McFarland & Co., 2012)
"Exploring a selection of CLAMP manga as well as anime it inspired, this volume examines CLAMP's broader philosophical underpinnings, its dedication to the invention of elaborate narrative constructs, its legendary passion for multilayered universes, and its symbolic interpretation of human identity as an unstable outcome of the intersection of science, fantasy and politics"--Provided by publisher.